Inter‐observer variability of experts and trainees for the diagnosis of reflux esophagitis: Comparison of linked color imaging, blue laser imaging, and white light imaging. Issue 7 (17th June 2021) - Lee, Sang Pyo; Kae, Sea Hyub; Jang, Hyun Joo; Koh, Dong Hee; Jung, Eun Suk
Abstract : Objectives: Diagnosis of reflux esophagitis according to the Los Angeles classification minimal change (LA‐M) has a low inter‐observer agreement. We aimed to investigate whether the inter‐observer agreement of reflux esophagitis was better when expert endoscopists read the endoscopic images, or when the linked color imaging (LCI) or blue laser imaging (BLI)‐bright mode was used. In addition, whether the inclusion of LA‐M in the definition of reflux esophagitis affected the consistency of the diagnosis was investigated. Methods: During upper endoscopy, endoscopic images of the gastroesophageal junction were taken using white light imaging (WLI), BLI‐bright, and LCI modes. Four expert endoscopists and four trainees reviewed the images to diagnose reflux esophagitis according to the modified LA classification. Results: The kappa values for the inter‐observer variability for the diagnosis of reflux esophagitis were poor to fair among the experts (κ =  0.22, 0.17, and 0.27 for WLI, BLI‐bright, and LCI, respectively) and poor among the trainees (κ =  0.18, 0.08, and 0.14 for WLI, BLI‐bright, and LCI). The inter‐observer variabilities for the diagnosis of reflux esophagitis excluding LA‐M were fair to moderate (κ =  0.42, 0.35, and 0.42 for WLI, BLI‐bright, and LCI) among the expert endoscopists and moderate among the trainees (κ = 0.48, 0.43, and 0.51 for WLI, BLI‐bright, and LCI). Conclusions: The inter‐observer agreement for the diagnosis of reflux esophagitis was very low for both the expert endoscopists and the trainees, even using BLI‐bright or LCI mode. However, when reflux esophagitis LA‐M was excluded from the diagnosis of esophagitis, the degree of inter‐observer agreement increased. Abstract : A total of 465 patients who received upper endoscopy for a medical check‐up were enrolled. Endoscopic images of gastroesophageal junction were taken in white light imaging (WLI), linked color imaging (LCI), and blue light imaging (BLI)‐bright modes. At least two endoscopic images in each mode were taken. When the four experts determined that the image quality was low, the case was excluded, Finally, the images from 388 patients were analyzed. The inter‐observer agreement for the diagnosis of reflux esophagitis was very low for both expert endoscopists and trainees, even using the BLI‐bright or LCI mode. However, when reflux esophagitis Los Angeles classification‐minimal change (LA‐M) was excluded from the diagnosis of esophagitis, the degree of inter‐observer agreement increased.